Water Footprint Analysis of Paddy Cultivation by Subsurface Irrigation in a Greenhouse - I Gede Pande Mahardika Pande; Chusnul Arif (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
Water is one of the main elements that rice plants require to grow and develop. The problem related to agricultural land is the shift in the function of agricultural land to become non-agricultural land due to competition in water usage. The water footprint approach can assess the amount of water required for production or yields. This study aims to analyze the water footprint value of rice cultivation with various treatments of irrigations. The research was conducted at the Kinjiro Farm Greenhouse, Gunung Batu, Bogor, West Java from March to July 2022. There were three treatments of irrigation systems based on water level, flooded irrigation (IT) with the water level above the soil surface, wet irrigation (IB) with the water level parallel to the soil surface, and dry irrigation (IK) with the water level below the soil surface. The total water footprint obtained for all treatments during rice cultivation activities was 9.73 m3/kg. The water footprint values ​​of IT, IB, and IK were 1.92 m3/kg, 1.66 m3/kg, and 6.14 m3/kg, respectively. IB had the largest water productivity of  0.60 kg/m3. Wet irrigation (IB) had the highest growth of rice plants based on the parameters of average growth of rice plant height, number of leaves, rice tillers, productive tillers, and rice panicles. Therefore, wet irrigation (IB) is the most optimal irrigation system for rice cultivation in a greenhouse.